A study of exposure to accidents at small roundabouts - Kamarulzaman Ibrahim (Universiti Kebangsaan Malaysia, 1997)
Traffic engineers often used the observed number of accidents to evaluate the safety of a particular site. However, if one were to compare a site with another in terms of safety, the use of accident frequency will be of a limited value since no account is taken of exposure to risk. In this study, three different measures of exposure to accidents at small roundabouts were compared. The first measure is the total number of traffic entering the roundabout. The other two measures are the product of cross flows at conflict points and the square root of the product of cross flows at conflict points. In modelling these measures of exposure in relation to accidents, generalised linear modelling technique was used. No conclusive answer was found on the most appropriate measure of exposure.